2021
DOI: 10.1002/anie.202104127
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Amplification of the Afterglow Luminescent Nanoreporter Enables the Prediction of Anti‐cancer Efficiency

Abstract: We developed ac yclic amplification method for an organic afterglow nanoreporter for the real-time visualization of self-generated reactive oxygen species (ROS). We promoted semiconducting polymer nanoparticles (PFODBT) as acandidate for emitting near-infrared afterglow luminescence.I ntroduction of ac hemiluminescent substrate (CPPO) into PFODBT (PFODBT@CPPO) resulted in as ignificant enhancement of afterglow intensity through the dual cyclic amplification pathway involving singlet oxygen ( 1 O 2 ). 1 O 2 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 55 publications
(20 reference statements)
0
63
0
Order By: Relevance
“…Moreover, ICG-loaded nanosystems also can activate ICD-associated cancer immunotherapy through induction of endoplasmic reticulum stress . Nevertheless, the inherent photobleaching and aggregation-caused quenching (ACQ) properties of ICG considerably reduce its singlet oxygen quantum yield ( Φ Δ ) and hence limit its PDT potency, causing weak ICD effect and suboptimal treatment of metastases. Nowadays, many strategies ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ICG-loaded nanosystems also can activate ICD-associated cancer immunotherapy through induction of endoplasmic reticulum stress . Nevertheless, the inherent photobleaching and aggregation-caused quenching (ACQ) properties of ICG considerably reduce its singlet oxygen quantum yield ( Φ Δ ) and hence limit its PDT potency, causing weak ICD effect and suboptimal treatment of metastases. Nowadays, many strategies ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, immunohistochemical analysis showed that a large amount of CD8 + T cell infiltration within tumor treated by Zn-Fu MNs, compared with PBS group (T cells indicated by arrows). Besides, the representative tumor sections were stained for apoptosis and necrosis analysis using the hematoxylin and eosin (H&E) 62 and terminal deoxynucleotidyl transferase mediated dUTP nick-end labeling (TUNEL) 63 . H&E and TUNEL stained tumor slice showed the obvious nuclear condensation and cell contour blurry in H&E observation and increasing green dots in TUNEL images, suggesting severe cell apoptosis and necrosis for tumor treated by Zn-Fu MNs (Figure 5 C).…”
Section: Resultsmentioning
confidence: 99%
“…We next optimized the incubation conditions of F1-GdNP for the detection of endogenous H 2 Sv ia epifluorescence imaging.T he intracellular fluorescence intensified with the incubation time or probesc oncentration, which reached ap lateau in RAW264.7 macrophages following incubation with F1-GdNP (28 mgmL À1 MEH-PPV) for 3h (Figure S13,14). Colocalization studies revealed ag ood overlap between the fluorescence of activated F1-GdNP at MEH-PPV channel and lysotracker,indicating the main distribution of F1-GdNP in the lysosomes after entry into RAW264.7 cells (Figure S15).…”
Section: Methodsmentioning
confidence: 97%